English in Context popular saying : An effective aid for vocabulary development - "Kirkpatrick, Betty" (Learners Publishing, 1999)
This book "contains 40 passages that cover a wide range of text types, different types of sayings, including clichés, colloquialisms, jargon and idioms. The book provides detailed explanations, example sentences, usage comments and origins, as well as suggesting simple alternatives where possible." - back cover
Keywords: English language